Broadening the foundation for the study of childhood connectedness to nature - Beery, Thomas; Djerf, Henric; Wünsche, Tanya Uhnger; Fridberg, Marie (Frontiers in Environmental Science, 2023)
The spatial aspect of these questions is considered as part of an investigation of school-age educare sites to facilitate nature experience and nurture the potential for connectedness to nature. While the standard for questions of connectedness to nature is to be studied at the individual level using methods such as psychometrics, observations, and interviews, less common are spatial methods applied to structural aspects of these questions. connectedness to nature study rarely considers the human relationship with nature across sociocultural/ structural/institutional levels. We present spatial analysis as a step toward a broader consideration of connectedness to nature. We promote the idea that careful consideration of connectedness to nature /disconnection must explore the forces beyond the individual shaping access and opportunity. This study provides a complex picture of access to nature for children in school-age educare sites in one Swedish city. The results also help highlight other aspects of access to nature experience coupled with spatial analysis.